Modelos y representaciones visuales en la ciencia - Gómez López, Susana (Escritura e Imagen, 2005)
An outstanding feature of modern science is their use of images. Their increasing use, both in scientific research processes and in communication media, contrasts with the short attention that Philosophy of Science has paid to them. The great amount of critics to the received view have left virtually untouched an assessment on the scientific images which continues to be present even in that historiography of science most away from positivistic views. In the latest years, however, some authors from very different research fields have been starting to show an increasing interest in scientific images, opening so new ways of analysis of their production and their function in scientific knowledge. In this article, I suggest an approach to the question that does not try to get closed conclusions or to establish a general interpretative thesis applicable to all types of scientific images. My target is to show some of the elements that have hindered the approach to the images in the philosophy of science in the XXth century, in order to move in a second place to analyze the usefulness and weaknesses of some philosophical alternatives for the comprehension of non verbal representation in science. At this point, an interesting approach proceeds from some versions of the semantic view which, highlighting the non linguistic nature of scientific models, points out the possibility of interpreting images as representational models. Even if I realize the value of some interpretative keys from these semantic views to study the non verbal representation in science, I try to show here how they suffer from certain weaknesses arising from basically two points: a too general and vague notions of scientific image and similarity. A classification of scientific images by their functions, their diagrammatic or naturalistic form, the visibility or invisibility of the object or phenomenon they represent is a necessary condition to begin a research about their actual making and their use in scientific practice. Meanwhile, this diversity reveals the plurality of uses of the concept of similarity, so raising once more one of the most classical questions of the theories of scientific representation.